The Effect of Mindfulness-based Self-compassion Training on Nurses’ Anger Management, Spiritual Well-being, and Job Involvement - Azra Zebardast; Nima Nateghian; Iraj Shakerinia (Journal of Client-centered Nursing Care)
Background: As a core part of the health care delivery system, nurses play a significant role in the evolution and progress of care, treatment, and promotion of health. Therefore, it is essential to prioritize their mental health and well-being. Teaching self-compassion to nurses can enhance their mental well-being and, consequently, improve the overall effectiveness of the healthcare system. We investigated the efficacy of self-compassion training on anger management, spiritual well-being, and job involvement of nurses. Methods: This research was a quasi-experimental study employing a pre-test, post-test design with a control group. The statistical population consisted of nurses working in various hospital departments affiliated with the University of Medical Sciences in Rasht City, Iran. Using available sampling, 26 nurses were selected and randomly assigned to either the control or experimental group (n=13 per group). The experimental group underwent eight 90-minute sessions of mindfulness-based self-compassion training over two months via virtual training, while the control group received no intervention. They voluntarily answered the demographic questionnaire, Buss-Perry aggression questionnaire (BPAQ), Paloutzian and Ellison spiritual well-being scale (SWBS), and Kanungo Job involvement questionnaire (JIQ). For data analysis, the independent t-test, chi-square, paired t-test, and multivariate analysis of covariance (MANCOVA) were used in SPSS software, version 21, at a significance level of 0.05. Results: The MANCOVA revealed that self-compassion training significantly reduced nurses’ anger and increased their spiritual well-being and job involvement (P<0.05). The eta-squared value showed that self-compassion training led to a 33% improvement in anger management, a 19% improvement in spiritual well-being, and a 23% improvement in job Involvement. Conclusion: Self-compassion training can enhance anger management, spiritual well-being, and job satisfaction among nurses. It is recommended that health policymakers consider implementing self-compassion training for all nurses to improve their mental health.